The Violation on Women’s Rights in the Unilateral Divorce in Sasak Community From A Feminist Legal Theory - Zulfatun Nimah (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2018)
For giving legal protection to both of husband and wife, Indonesian Marriage Act 1/1974 regulate that a divorce should be done in the court. However, until recently there are many Sasak men still divorced their wives by unilateral statement only, not through trial process in the court. From a feminist legal theory perspective, the practice of unilateral divorce was susceptible to violate women’s right because empirically the living law in the community is generally formulated by male figures, using man perspective and aim for perpetuate men power. This research aims to describe and analyse the forms of violation of the rights of Sasak women who was unilaterally divorced by her husband. This research is a type of empirical legal research using qualitative approach. Primary data is taken from the subject of research, by in-depth interview technique and non-participatory observation. The result of research shows that there are four types of violation on women’s rights who are divorced by their husband, namely: a) not getting mut’ah (competation of divorce) and basic necessity during `iddah; b) not getting the settlement for mahr; c) not getting the share of community property; and d) not having certain marital status. Base on this result, it is very important to conduct a legal literacy program for Sasak community for make them not divorce unilaterally anymore.